Nanostructured Conductive Polymers 2010
DOI: 10.1002/9780470661338.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Aspects of Conducting‐Polymer Actuators

Abstract: Dimensional changes in conducting polymers such as polypyrrole (PPy), polyaniline (PANI), and poly(3,4-ethylenedioxythiophene) (PEDOT) during oxidation and reduction have been used for over 15 years to create movement, an actuating effect. This has opened up the possibility of the development of a new class of polymer-based, large strain, artificial muscles, to stand alongside other prospective materials, such as dielectric elastomers, shape-memory alloys, and carbon nanotube fibers [1]. Advantages of conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…This phenomenon has been proposed to be exploitable for a new generation of actuators. CP actuation can be chemically and electrochemically controlled [ 102 ]. Representatively, the mechanism of the electrochemical actuation in CPs is illustrated in Figure 9 .…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been proposed to be exploitable for a new generation of actuators. CP actuation can be chemically and electrochemically controlled [ 102 ]. Representatively, the mechanism of the electrochemical actuation in CPs is illustrated in Figure 9 .…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…In addition to tailoring the properties of the main components, such the CP and electrolytes, it is very important to design efficient actuating systems for significant improvement of the performance of CP-based soft actuators. Several remarkable actuating systems have been designed, such as bilayer-trilayer actuators, out-of-plane actuators, and linear actuators [ 102 ].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Sir: Gu et al have fabricated an electrochemical actuator based on a polymeric nanofibrous bundle for use as artificial muscle. It is well known that the actuation of intrinsically conducting polymers is due to the movement of ions and solvent in and out of the polymer during oxidation and reduction processes . Thus, as a part of electrochemical studies, the cyclic voltammetric behavior has been interpreted by the classic Randles−Sevcik equation.…”
mentioning
confidence: 99%
“…This can be attributed to the electrochemical redox reaction mechanism that drives the PPy actuators. When the PPy backbone undergoes electrochemical oxidation, it becomes positively charged, and the anion from the electrolyte is incorporated into the film as a dopant, leading to elongation of the PPy main chain [ 37 , 38 , 39 , 40 , 41 , 42 ]. Accordingly, it is revealed that the polymerization conditions, especially the choice of electrolyte and solvent, have a significant impact on actuator performance.…”
Section: Resultsmentioning
confidence: 99%